AGROTECHNOLOGY OF WINTER CABBAGE SEED PRODUCTION IN CONDITION OF DAGESTAN - N. M. Velizhanov; M. M. Abdulaev (Овощи России)
Soil-climatic conditions of the South region of Dagestan are suitable for growing of winter cabbage. The yield of winter cab-bage in Dagestan farms is still very low because of low quality of seeds and non'observance of rules of cabbage seed production.